2023
DOI: 10.1093/bioinformatics/btad073
|View full text |Cite
|
Sign up to set email alerts
|

DeepPheWAS: an R package for phenotype generation and association analysis for phenome-wide association studies

Abstract: Summary DeepPheWAS is an R package for phenome wide association studies that creates clinically-curated composite phenotypes, and integrates quantitative phenotypes from primary care data, longitudinal trajectories of quantitative measures, disease progression, and drug response phenotypes. Tools are provided for efficient analysis of association with any genetic input, under any genetic model, with optional sex-stratified analysis, and for developing novel phenotypes. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…To supplement understanding of the biological pathways and clinical phenotypes influenced by TSH-associated variants, we first tested associations with circulating free T 4 levels, hypothyroidism, hyperthyroidism ( Figure 1, Supplementary Table 4 ), thyroid cancer and other thyroid disease. Using DeepPheWAS(7), we then undertook PheWAS of selected individual variants which mapped to putative causal genes implicated by ≥3 criteria or by a single putative causal missense variant (posterior probability >50%; Supplementary Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To supplement understanding of the biological pathways and clinical phenotypes influenced by TSH-associated variants, we first tested associations with circulating free T 4 levels, hypothyroidism, hyperthyroidism ( Figure 1, Supplementary Table 4 ), thyroid cancer and other thyroid disease. Using DeepPheWAS(7), we then undertook PheWAS of selected individual variants which mapped to putative causal genes implicated by ≥3 criteria or by a single putative causal missense variant (posterior probability >50%; Supplementary Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Through the most comprehensive initiative to identify putative causal variants and genes for TSH levels, we defined 112 high confidence genes implicated by multiple criteria. This is the first study to develop pathway-specific GRS for TSH levels and to use these in PheWAS, through our new DeepPheWAS platform(7), to investigate the potential consequences of intervening in relevant pathways. It is also the first to develop and use a polygenic score to predict age of onset of hypothyroidism and hyperthyroidism, showing marked differences in ages of onset of these conditions according to PGS deciles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The next-generation sequencing (NGS) of human genomes provides a combination of genetic and phenotypic data that is boosting drug discovery efforts by providing human-relevant efficacy and safety signals. The initial report that TRPM8 is linked to migraine [ 7 ] is now confirmed by UK and FinnGEN Biobank data [ 8 , 9 , 10 ], strongly supporting the role of TRPM8 in migraine pathogenesis. The first clinical study in healthy volunteers with a selective TRPM8 antagonist by Pfizer revealed that TRPM8 antagonists are able to alleviate cold pressor test-induced pain.…”
mentioning
confidence: 77%
“…Top SNPs that were not reported in the largest GWAS of lung function to date (r 2 ≥0.5) were reported as novel for both PRISm and lung function [ 8 ]. The SNPs were analysed using deep PheWAS enriched for lung function traits to examine for associations with lung function and other traits [ 19 ]. The nearest genes to these novel SNPs were then investigated for gene ontology information using the Functional Mapping and Annotation of Genome-wide association studies (FUMA) tool ( https://fuma.ctglab.nl ).…”
Section: Methodsmentioning
confidence: 99%